Clinical and genetic analysis of pediatric patients with Wilson disease - Şimşek Papur, Özlenen; Aşık Akman, Sezin; Terzioğlu, Orhan (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Wilson disease (WD, MIM# 277900) is an autosomal recessive disorder of copper transport resulting from the defective function of a copper transporting P-type ATPase. Detecting mutations and single nucleotide polymorphisms (SNPs) of the ATP7B gene in Turkish pediatric WD patients (n=32) and controls (n=52) is the aim of this research. Materials and Methods: For screening mutations and SNPs of the ATP7B gene, sequencing was performed. Results: Mutations were determined in the ATP7B gene in 23 out of the 32 pediatric patients. The mutation detection rate in the ATP7B gene of the pediatric Turkish WD patients was 71.875%. Fifteen different mutations were determined in the ATP7B gene. These mutations were distributed throughout the ATP7B gene and were as follows: 2 deletion, 1 insertion, 3 nonsense, and 9 missense mutations. Four of these, including c.3111delC (1 deletion) and c.2363C>T, c.3733C>A, and c.3451C>T (3 missense) mutations, were detected in the Turkish WD patients. Eleven polymorphisms were detected in both groups. Among these, c.3727G>A (SNP) was reported in the Wilson Disease Mutation Database by our group. Nine out of the thirty-two pediatric Turkish WD patients had no mutations in the ATP7B gene. Conclusion: To find the cause of WD in pediatric patients who have no mutation in ATP7B, additional research is necessary.